Molecular Pathogenesis of Gene Regulation by the miR-150 Duplex: miR-150-3p Regulates TNS4 in Lung Adenocarcinoma - Misono, Shunsuke (Cancers (Basel), 2019)
Based on our miRNA expression signatures, we focused on miR-150-5p (the guide strand) and miR-150-3p (the passenger strand) to investigate their functional significance in lung adenocarcinoma (LUAD). Downregulation of miR-150 duplex was confirmed in LUAD clinical specimens. In vitro assays revealed that ectopic expression of miR-150-5p and miR-150-3p inhibited cancer cell malignancy. We performed genome-wide gene expression analyses and in silico database searches to identify their oncogenic targets in LUAD cells. A total of 41 and 26 genes were identified as miR-150-5p and miR-150-3p targets, respectively, and they were closely involved in LUAD pathogenesis. Among the targets, we investigated the oncogenic roles of tensin 4 (TNS4) because high expression of TNS4 was strongly related to poorer prognosis of LUAD patients (disease-free survival: p = 0.0213 and overall survival: p = 0.0003). Expression of TNS4 was directly regulated by miR-150-3p in LUAD cells. Aberrant expression of TNS4 was detected in LUAD clinical specimens and its aberrant expression increased the aggressiveness of LUAD cells. Furthermore, we identified genes downstream from TNS4 that were associated with critical regulators of genomic stability. Our approach (discovery of anti-tumor miRNAs and their target RNAs for LUAD) will contribute to the elucidation of molecular networks involved in the malignant transformation of LUAD.